2003
DOI: 10.1074/jbc.m212003200
|View full text |Cite
|
Sign up to set email alerts
|

Folding Pathway Mediated by an Intramolecular Chaperone

Abstract: Catalytic domains of several prokaryotic and eukaryotic protease families require dedicated N-terminal propeptide domains or ''intramolecular chaperones'' to facilitate correct folding. Amino acid sequence analysis of these families establishes three important characteristics: (i) propeptides are almost always less conserved than their cognate catalytic domains, (ii) they contain a large number of charged amino acids, and (iii) propeptides within different protease families display insignificant sequence simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Alignment of known IMC sequences from subtilases helped identify two small hydrophobic motifs, N1 and N2, that appear to be conserved within such propeptides (70). Interestingly, when one compares the IMC sequence from subtilisin E with aqualysin, POIA1 (71), or with a designed peptide chaperone ProD which was computationally forced to diverge from the IMC of subtilisin, a high degree of sequence conservation appears isolated within motifs N1 and N2 (72). Random mutagenesis using error-prone PCR along with an activity-based genetic screening technique demonstrated that substitutions within motifs N1 and N2 were often deleterious (73, 74).…”
Section: The Concept Of Intramolecular Chaperonesmentioning
confidence: 99%
See 2 more Smart Citations
“…Alignment of known IMC sequences from subtilases helped identify two small hydrophobic motifs, N1 and N2, that appear to be conserved within such propeptides (70). Interestingly, when one compares the IMC sequence from subtilisin E with aqualysin, POIA1 (71), or with a designed peptide chaperone ProD which was computationally forced to diverge from the IMC of subtilisin, a high degree of sequence conservation appears isolated within motifs N1 and N2 (72). Random mutagenesis using error-prone PCR along with an activity-based genetic screening technique demonstrated that substitutions within motifs N1 and N2 were often deleterious (73, 74).…”
Section: The Concept Of Intramolecular Chaperonesmentioning
confidence: 99%
“…To explore this possibility, the sequence–structure relation within subtilases was analyzed (72). It is easier to reconcile the differences in the extent of sequence conservation among the IMCs and their cognate protease domains in different protein families.…”
Section: The Concept Of Intramolecular Chaperonesmentioning
confidence: 99%
See 1 more Smart Citation
“…CD analyses were performed on an automated AVIV 215 spectrometer at 25 °C as described previously (27). All the protein concentrations were maintained at 0.1 mg/ml.…”
Section: Circular Dichroismmentioning
confidence: 99%
“…16,17) In a study of serine protease subtilisins and their propeptides, the functions of subtilisin propeptides as intramolecular chaperons and inhibitors were identified, [18][19][20] and the structure of the subtilisinpropeptide complex was also determined. 20) Structural analysis indicated that the C-terminal strand of the propeptide binds to the subtilisin substrate-binding cleft.…”
Section: Discussionmentioning
confidence: 99%